The Future of Technology Education - Williams, P John (Springer, 2016)
Twenty-five years ago there was increasing optimism in policy, curriculum and research about the contribution that technology education might make to increased technological literacy in schools and the wider population. That optimism continues, although the status of technology as a learning area remains fragile in many places.